Family Day Care Handbook - Community Coordinated Child Care (4-C) in Dane County, Inc., Madison, WI.; Community Coordinated Child Care (4-C) in Dane County, Inc., Madison, WI. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1974)
This handbook provides both general and specific information on child development and child care to help adults who are providing child care in their homes. Information is presented in six sections which describe: (1) the family day care system, the occupation of caregiver, and the development of relationships; (2) development of a health program, recognizing and dealing with illness and emergencies, safety, and community health resources; (3) nutrition, meal-planning, and nutrition resources; (4) child growth and development, methods to encourage growth, and recognition of special problems; (5) use of the caregiver's time, home, and skills in child care; and (6) organization and record keeping. The purpose of the handbook is to give the caregiver a better understanding of the job of child care, ideas for planning for care, activity suggestions, and ways of assessing the job being done. An outline format with illustrative examples makes this handbook particularly useful. (SDH)
Sponsoring Agency: Office of Child Development (DHEW), Washington, DC.
Sponsoring Agency: Wisconsin State Dept. of Health and Social Services, Madison.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Child Care; Child Caregivers; Child Development; Childhood Needs; Community Resources; Family Day Care; Guides; Health Services; Home Programs; Learning Activities; Nutrition; Play; Program Development; Recordkeeping; Safety; Guides, General